Effects add kefir grains to whey cheese on chemical and microbiological qualities - Hilmi, Mustofa; Prastujati, Anis Usfah; Khusna, Asmaul; Khirzin, Muhammad Habbib; Yannuarista, Deni (Faculty of Animal Science, Universitas Brawijaya, 2019)
Whey is liquid cheese waste produced from the cheese making process after being separated from the curd. Cheese production waste contains a carbon source, one of which is lactose as an energy source in the development of fermented biotechnology, especially the manufacture of probiotics for livestock. Lactose (4-7%) and protein (0.6-1%) in whey cheese can be used as a medium for the growth of lactic acid bacteria and yeast in producing secondary metabolites which could be applied as nutraceutical feed additives that were useful for medical or health, including prevention and treatment of diseases and improve livestock performance.The research purpose was to determine the effect of adding kefir grain 1-5% into whey cheese based on chemical quality and microbiological. Whey Cheese is mixed with 10% molasses and then heated at 80oC for 10 minutes later the temperature is lowered between 35-40 oC and added starter according to treatment. The next step is incubating anaerobic kefir fermentation for 24 hours with temperatures between 35-40oC. The experimental method was designed with a completely randomized design with 6 starter level treatments and 3 replications, namely 0%, 1%, 2%, 3%, 4%, 5%. The results showed that the addition of 1-5% kefir grain was very significant (P<0.01) increasing protein, lactic acid bacteria, yeast and reducing water, fat, Total Plate Count (TPC). It can be concluded study concludes that the addition of 5% kefir grain into whey cheese added with 10% molasses affects the increase in lactic and yeast acid bacteria, protein and decreases fat, water, Total Plate Count (TPC).